Design and Operation Parameters of Vibrating Harvester for Coffea arabica L. - Yingjie Yu; Ying Cao; Qinghui Lai; Qinghui Zhao; Zhexing Sun; Shengwu Zhou; Dake Song (Agriculture, 2023)
This study designed a handheld vibrating coffee harvester to improve the mechanized harvesting of Coffea arabica L. The proposed device was used to vibrate branches of Coffea arabica L. trees, and the shedding of coffee fruit and the operation parameters of vibrational harvesting were analyzed. Images captured using high-speed photography were used to derive a force equation that represents the forced vibration of the coffee fruit-stalk joint. In addition, the vibrations of coffee berries and branches were theoretically analyzed, and the results were used to establish a dynamic vibration model of coffee trees. The shedding of coffee berries was primarily affected by the vibration frequency, vibration amplitude, and excitation position, which were simulated using a rigid–flexible branch-machine coupling model on RecurDyn software. Furthermore, field experiments were conducted to determine the optimal working parameters for coffee harvesting using vibrations. The results indicated optimal picking performance when the vibration frequency, vibration amplitude, and excitation position were 62 Hz, 9 mm, and 0.4 L, respectively. The harvesting rates of ripe and unripe coffee were 92.22% and 8.33%, respectively, and the damage rate was 5.23%. Thus, the proposed harvester can satisfactorily achieve the optimal harvesting of Coffea arabica L.